Mapping the cloud: Big Tech taking the sky by storm - Cecilia Rikap (City, University of London, City Political Economy Research Centre (CITYPERC), 2023)
Here I map Big Tech clouds focusing on the making of asymmetric relations with the different type of involved organizations. Amazon, Microsoft, Google and Alibaba are cloud hegemons that control every inch of their clouds. The cloud is the main means of adoption of digital technologies. As such, developers and other firms offering their services on Big Tech clouds accept the rules of a game predefined by those few giants. They even need to get enabling credentials offered by another type of subordinate actor: the companies offering trainings to get mandatory certificates for joining the cloud as providers. At the other end, customers transition to the cloud often guided and hiring the services of outsourced sales forces. After presenting all these actors and their interplay, I focus on AI as a service to explain the negative effects of such a migration at the level of organizational learning and innovation. Customers' technological subordination and reduced learning by doing, using and interacting in the cloud has triggered mitigation strategies but only large players can afford them.
Keywords: 330; Cloud computing; digital technologies; Big Tech; corporate power; digital learning; learning by doing